2022
DOI: 10.3390/pharmaceutics14030473
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Appropriateness of Formulations on the WHO Model List of Essential Medicines for Children: Development of a Paediatric Quality Target Product Profile Tool

Abstract: The World Health Organization’s Model List of Essential Medicines for Children (EMLc) presents a list of the most efficacious, safe, and cost-effective medicines for priority conditions, intended for use in children up to 12 years of age. However, gaps in global availability and use of age-appropriate formulations of medicines for children still exist. To address these shortcomings, a comprehensive analysis of the appropriateness of formulations of essential medicines for children is being undertaken through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Moreover, compared to a classic QTPP, it includes characteristics that have a higher impact on the paediatric patient and the efficacy and safety of their treatment, such as palatability. Walsh et al have developed a model pQTPP, along with a risk score-based tool previously conceptualised by the WHO, to identify whether the medicines in the pre-development or development phase, as well as the already existing products containing APIs included in the Model List of Essential Medicines for Children, are fit for paediatric pharmacotherapy [77].…”
Section: Quality Profile Of Odx For Paediatric Usementioning
confidence: 99%
“…Moreover, compared to a classic QTPP, it includes characteristics that have a higher impact on the paediatric patient and the efficacy and safety of their treatment, such as palatability. Walsh et al have developed a model pQTPP, along with a risk score-based tool previously conceptualised by the WHO, to identify whether the medicines in the pre-development or development phase, as well as the already existing products containing APIs included in the Model List of Essential Medicines for Children, are fit for paediatric pharmacotherapy [77].…”
Section: Quality Profile Of Odx For Paediatric Usementioning
confidence: 99%
“…4 Walsh et al also identified a major gap to dose young children and confirmed by clinicians’ experience, given the difficulty in manipulating the contents of the capsule. 5 There is also a need for alternative formulations that meet the needs of patients with dysphagia or those who are intubated.…”
mentioning
confidence: 99%
“…The tool uses reports of direct observation of attempted/successful administration to confirm and thus expand upon the ages of children and reasons why a medicine may either be classified as AaF or AiF [ 23 , 27 29 ]. The classification ‘Maybe age-appropriate’ indicates that the DF was either authorised but used OL or was an UL medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported assessment of AaFs [ 22 , 23 , 38 , 45 , 46 ] by screening lists of medicinal products according to set criteria or making assumptions for the expected ‘user’; in terms of generic age/weight band profiles and the anticipated physical capability of a child, consistent with paediatric developmental milestones. One such assumption is that children under 6 years are unable to swallow SODFs such as tablets, which is not the case [ 47 ].…”
Section: Discussionmentioning
confidence: 99%